Identification of Specific Circular RNA Expression Patterns and MicroRNA Interaction Networks in Mesial Temporal Lobe Epilepsy - Gray, Lachlan G.; Mills, James D.; Curry-Hyde, Ashton; Devore, Sasha; Friedman, Daniel; Thom, Maria; Scott, Catherine; Thijs, Roland D.; Aronica, Eleonora; Devinsky, Orrin; Janitz, Michael (Frontiers in Genetics, 2020)
Circular RNAs (circRNAs) regulate mRNA translation by binding to microRNAs (miRNAs) and their expression is altered in diverse disorders, including cancer, cardiovascular disease and Parkinson’s disease. Here, we compared circRNA expression patterns in temporal cortex and hippocampus from patients with pharmacoresistant mesial temporal lobe epilepsy (MTLE) and healthy controls. Nine circRNAs showed significant differential expression, including circRNA-HOMER1, which is expressed in synapses. Further, we identified enriched miRNA binding sites within the sequences of differentially expressed circRNAs; expression levels of mRNAs correlated with changes in complementary miRNAs. Gene ontology enrichment analysis of mRNA targets revealed biological processes, including axon guidance, transmembrane transport and axonogenesis, critical in maintaining the structure and function of hippocampal neurons. The circRNA-miRNA-mRNA interaction networks illuminates the molecular changes in MTLE, which may be pathogenic or an effect of the disease or treatments and suggests that differentially expressed circRNAs and associated miRNAs may be novel therapeutic targets.